1988
DOI: 10.7326/0003-4819-108-6-800
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Occlusion Pressure: A Simple Index to Monitor Respiratory Muscle Fatigue during Acute Respiratory Failure in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Extubation should not be done in patients with respiratory muscle fatigue despite improvement in arterial blood gases and clinical status; and P0.1 provides a valid and simple index to assess the likelihood of respiratory muscle fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(44 citation statements)
references
References 18 publications
4
38
1
1
Order By: Relevance
“…The increased P0.1 during ARF is in agreement with previous studies [22]. Although P0.1 was larger in FW compared to SW patients, in contrast to other studies [23][24][25], the difference in mean P0.1 between these groups did not achieve statistical significance. Similarly, P0.1/PI,max did not separate the FW and SW patients.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…The increased P0.1 during ARF is in agreement with previous studies [22]. Although P0.1 was larger in FW compared to SW patients, in contrast to other studies [23][24][25], the difference in mean P0.1 between these groups did not achieve statistical significance. Similarly, P0.1/PI,max did not separate the FW and SW patients.…”
Section: Discussioncontrasting
confidence: 36%
“…The predictive value of P0.1 to indicate FW or SW has been questioned by others [26], who were only able to separate FW and SW patients by a difference in hypercapnic augmentation of P0.1. Nevertheless, most studies [22][23][24][25] have demonstrated that neuromuscular output is augmented in ARF and FW patients. It should be emphasized that the present study did not address the utility of these measured variables in predicting weaning outcome, but they were used to assess differences in the physiological characteristics between FW patients and those with ARF.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that during spontaneous breathing trials COPD patients may exhibit markedly enhanced dynamic hyperinflation (DH) with concomitant decrease in Crs,st. This enhanced DH is closely associated with weaning failure [19,20]. This may explain why Crs,st as well as Crs,eff, measured during mechanical ventilation, are of poor predictive power for weaning outcome (table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts at weaning had resulted in hypercapnic respiratory failure in all patients. Entry into the study occurred when (1) Maximum relaxation rate of the diaphragm during weaning from mechanical ventilation p<0-001) and PDi (p<0001). MRR was not different from the control value by the fourth minute for POES and PDi (fig 1).…”
Section: Normal Subjectsmentioning
confidence: 99%